Here,
I=intdx/[2cos²x+3cosx]
=int1/(cosx(2cosx+3))dx
=1/3int3/(cosx(2cosx+3))dx
=1/3int[(2cosx+3)-2cosx)/(cosx(2cosx+3))dx
=1/3int[1/cosx-2/(2cosx+3)]dx
=1/3color(red)(intsecxdx)-2/3int1/(2cosx+3)dx...tocolor(red)(Apply(1)
=1/3color(red)(ln|secx+tanx|)-2/3I_1...to(A)
Now, I_1=int1/(2cosx+3)dx
Let, color(violet)(tan(x/2)=t)=>sec^2(x/2)1/2dx=dt
=>(1+tan^2(x/2))dx=2dt=>dx=(2dt)/(1+t^2)
So,
I_1=int2/(2((1-t^2)/(1+t^2))+3)xx1/(1+t^2)dt
=2int1/(2-2t^2+3+3t^2)dt
=2intcolor(blue)(1/(t^2+(sqrt5)^2)dt...tocolor(blue)(Apply(2)
=2color(blue)([1/sqrt5tan^-1(t/sqrt5)])+c
Subst. back ,color(violet)(t=tan(x/2)
I_1=2/sqrt5tan^-1(tan(x/2)/sqrt5)+c
From (A) ,we get
I=1/3ln|secx+tanx|-2/3xx2/sqrt5tan^-1(tan(x/2)/sqrt5)+C
I=1/3ln|secx+tanx|-4/(3sqrt5)tan^-1(tan(x/2)/sqrt5)+C
Note : Formulas.
color(red)((1)intsecxdx=ln|secx+tanx|+c
color(blue)((2)int1/(x^2+a^2)dx=1/atan^-1(x/a)+c